Listeria spp. in the coastal environment of the Aqaba Gulf, Suez Gulf and the Red Sea - EL-SHENAWY, MOUSTAFA A. (Cambridge University Press, 2006)
Listeria monocytogenes is an important pathogen which causes an infection called listeriosis. Because of the high mortality rate (∼30%) associated with listeriosis, and the widespread nature of the organism, it is a major concern for food and water microbiologists since it has been isolated from various types of foods, including seafood, as well as from the aqueous environment. To investigate the prevalence of this pathogen in the Aqaba Gulf (12 sites), Suez Gulf (14 sites) and Red Sea (14 sites), 200 water samples (collected during five sampling cruises in 2004), 40 fresh fish samples and 15 shellfish samples were analysed using the enrichment procedure and selective agar medium. All water samples were also examined for the presence Listeria innocua which was the most common of the Listeria spp. isolated, followed by L. monocytogenes, with a low incidence of the other species. During the whole year, the percentage of Listeria spp. and L. monocytogenes in 200 water samples was 20·5% (41 samples) and 13% (26 samples) respectively. In fresh fish (40 samples) it was 37% (15 samples) and 17·3% (7 samples) and in shellfish (15 samples) 53% (8 samples) and 33% (5 samples) respectively. In water samples, there was an association between the faecal contamination parameters and the presence of the pathogen; however, water salinity, temperature, dissolved oxygen and pH did not influence the occurrence of this bacterium. These results may help in the water-quality evaluation of the coastal environments of these regions.